Television news in Bangladesh: intersection of market-oriented journalism and perceived credibility - Andaleeb, Syed Saad; Rahman, Anis (© 2014 AMIC/SCI-NTU.Routledge, 2016)
This article was published in the Asian Journal of Communication [©2014 Published by AMIC/SCI-NTU. Routledge] and the definite version is available at: http://doi.org/10.1080/01292986.2014.946064 The Article's website is at: http://www.tandfonline.com/doi/abs/10.1080/01292986.2014.946064